Cuestiones prejudiciales en la Unión Europea y consultas prejudiciales en la Comunidad Andina: Similitudes, diferencias e influencias - Manuel Cienfuegos Mateo (Revista Electrónica de Estudios Internacionales, 2013)
The objective of this research is to compare the legal regime of the European Union preliminary ruling procedure and the Andean Community preliminary consultation procedure. To this end, the current normative and the functioning in practice of both procedural instruments are described, focusing the analysis on the more important aspects, such as their nature; legal standing as well as powers of national jurisdictions; competences of the European and the Andean Courts of Justice in every preliminary procedure; procedural aspects and, finally, legal effects of preliminary rulings and remedies to their breach. Following the explanation of the Andean preliminary consultation procedure, the main similarities and differences between these two judicial cooperation mechanisms will be noted in order to offer, at the end of the study, some conjectures for the significant influence of the European preliminary ruling on that.